Strengthening the Profile of Pancasila Students in the Dimension of Global Diversity Through a CRT Approach Based on Bekakak Sculpture Art - Tiza Ariesta Saputri; Chairul Kusuma Anjani; Rima Devita Sari; Insanul Qisti Barriyah; Heri Maria Zulfiati; Ana Fitrotun Nisa (Universitas Pendidikan Ganesha, 2025)
Contemporary education needs to position Culturally Responsive Teaching (CRT) as a central approach for strengthening the global diversity dimension of the Pancasila Student Profile, particularly through the integration of local cultural arts such as traditional sculpture. However, classroom practices still do not fully reflect these principles. This study aims to explore how CRT, when combined with art-based activities, can foster students’ tolerance, empathy, and appreciation for diverse cultural perspectives. This research employs a qualitative descriptive approach with a case-study design involving a group of early-grade elementary students. Data were gathered through participatory observations, in-depth interviews, student reflective journals, and documentation of their artwork. The analysis process followed the stages proposed by Miles and Huberman, including data reduction, data display, and verification of emerging findings. The results indicate that most students were actively engaged throughout the learning process, developed a deeper understanding of cultural diversity, and demonstrated more inclusive collaborative behaviors. The use of traditional sculpture as a learning medium supported students in connecting local cultural values with universal principles such as respect, empathy, and cooperation. The study concludes that implementing CRT through culturally meaningful art activities is effective in enhancing students’ awareness of global diversity. These findings highlight the importance of integrating local cultural arts as a pedagogical strategy to strengthen students’ character formation and global competencies.